Does the Theory of Planned Behavior Predict Dietary Sodium Intake in Patients With Heart Failure?. (April 2017) - Wu, Jia-Rong; Lennie, Terry A.; Dunbar, Sandra B.; Pressler, Susan J.; Moser, Debra K.
Sodium intake in heart failure (HF) is a crucial but poorly understood phenomenon. Theoretical models promote understanding and provide a context for rational appraisal of complex situations. The purpose of this study was to determine which factors were associated with sodium intake in HF patients using theory of planned behavior (TPB). In this study, patients' ( N = 244) attitudes, subjective norms, and perceived behavioral control (tenets of the TPB) were assessed using the Dietary Sodium Restriction Questionnaire. Sodium intake was estimated objectively by 24-hr urinary sodium excretion (UNa). The average UNa was 3, 811 mg. Subjective norms, gender, and New York Heart Association functional class were associated with sodium intake ( p < .001). Thus, it is important for health care providers to clearly express their approval of following low-sodium diet to their HF patients, and include significant others in interventions to help patients develop/maintain a positive subjective norm to decrease sodium intake and reduce HF exacerbations.